2010
DOI: 10.1190/1.3506039
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution reservoir characterization by an acoustic impedance inversion of a Tertiary deltaic clinoform system in the North Sea

Abstract: Fluvio-deltaic sedimentary systems are of great interest for explorationists because they can form prolific hydrocarbon plays. However, they are also among the most complex and heterogeneous ones encountered in the subsurface, and potential reservoir units are often close to or below seismic resolution. For seismic inversion, it is therefore important to integrate the seismic data with higher resolution constraints obtained from well logs, whereby not only the acoustic properties are used but also the detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…According to Figure 2, the horizon of interest is at an interval rich in sediments with gamma ray values generally greater than 70 API [45]. This is consistent with the observation of Tetyukhina, et al [8] who reported that shaly sediments with higher impedance values were deposited mainly at the bottomset of the clinoform system in the F3 block of the Southern North Sea basin.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…According to Figure 2, the horizon of interest is at an interval rich in sediments with gamma ray values generally greater than 70 API [45]. This is consistent with the observation of Tetyukhina, et al [8] who reported that shaly sediments with higher impedance values were deposited mainly at the bottomset of the clinoform system in the F3 block of the Southern North Sea basin.…”
supporting
confidence: 83%
“…Channels are generally visually close to or below seismic resolution [7,8], so thin to their surrounding geometry that their subtleties are nearly invisible in traditional seismic data. Thus, delineating thin reservoir sands from conventional seismic data had always been a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The North Sea Groups of Cenozoic era, approximately 1460 m in total thickness unconformably overlying the Chalk Group of Late Cretaceous. In North Sea region thermally subsiding basin (epicontinental basin received sediments from neighboring landmasses), were formed during Cenozoic era (Sclater and Christie 1980;Ziegler 1988;Jordt et al 1995;Sørensen et al 1997;Faleide et al 2002;Tetyukhina et al 2010;Benvenuti et al 2012;Mojeddifar et al 2015; Figure 1. Location map of F3-block: (a) subset of coordinate reference system ED50-UTM31, (b) Netherlands onshore and offshore boundaries and structural elements of the Late Jurassic-Early Cretaceous, modified after (Schroot and Schüttenhelm 2003;Kombrink et al 2012;Nelskamp et al 2012), (c) the seismic survey boundary of F3-block in blue, the location of the wells by black dots and the north-south and east-west cross sections by dashed lines.…”
Section: Geological Settingmentioning
confidence: 99%
“…In the oil and gas industry, inversion of seismic data is a well-known technique used for refining structural interpretation as well as for reservoir characterization (Treitel and Lines, 2001;Tetyukhina et al, 2010). With continued progress in computing power and seismic data acquisition, the seismic full-waveform inversion technique introduced by Tarantola (1984), in which all wave types including multiscattered waves are accounted for, is becoming feasible.…”
Section: Introductionmentioning
confidence: 99%